2016
DOI: 10.1007/s00737-016-0621-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in self-reported difficulty sleeping across the menstrual cycle

Abstract: The effect of menstrual cycle phase on sleep has been studied for decades; however, individual differences in the associations between sleep and menstrual phase have not been well studied. In addition, the associations between changes in sleep and other physiological and psychological factors that vary as a function of menstrual phase have not been thoroughly assessed. This study explored individual differences in daily self-reports of difficulty sleeping across the menstrual cycle, as well as associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…The results of logistic regression analysis in Table 3 indicates that adolescents who have poor sleep quality have an opportunity to experience irregular menstrual cycles 2.05 times compared to those with good sleep quality. This is in line with the research conducted by Romans [11] that there is a relationship between the quality of sleep and the menstrual cycle, menstruating women have been reported to have poorer sleep quality and greater sleep disturbance [21][22][23]. According to Kloss et al [24], there is a significant relationship in the research between the quality of sleep and the menstrual cycle because hormones will be processed during sleep.…”
Section: The Relationship Between Bmi Sleep Quality Stress Conditions and Menstrual Cyclessupporting
confidence: 81%
“…The results of logistic regression analysis in Table 3 indicates that adolescents who have poor sleep quality have an opportunity to experience irregular menstrual cycles 2.05 times compared to those with good sleep quality. This is in line with the research conducted by Romans [11] that there is a relationship between the quality of sleep and the menstrual cycle, menstruating women have been reported to have poorer sleep quality and greater sleep disturbance [21][22][23]. According to Kloss et al [24], there is a significant relationship in the research between the quality of sleep and the menstrual cycle because hormones will be processed during sleep.…”
Section: The Relationship Between Bmi Sleep Quality Stress Conditions and Menstrual Cyclessupporting
confidence: 81%
“…Less obvious are the physiological processes inside the body such as the rhythmicity of the sex hormones that drive the menstrual cycle and others that regulate growth and metabolism 1 . These rhythms also interact with each other through synchronization of cellular activities with the external environment through feedback mechanisms that promote dynamic stability, such as the interaction between circadian rhythms, sleep and the menstrual cycle 2 , 3 . Perturbations of the body’s rhythmic processes are associated with disorders 4 such as disturbed circadian rhythmicity with premenstrual dysphoric disorder (PMDD) 5 or abnormal expression of the circadian clock gene and spontaneous abortion 6 .…”
Section: Introductionmentioning
confidence: 99%
“…She did not have a sleeping partner or dependent and, therefore, was solely responsible for her own sleep, nutrition, and schedule. KW had normal menses, no menses during the trial, and self-reported no history of interaction between sleep quality and menstrual cycle phases [31,32]. Hence, we did not record whether or when she menstruated during the intervention period.…”
Section: Resultsmentioning
confidence: 99%